An Integrated Analysis of Key Factors Influencing Customer Satisfaction in Asian Low-Cost Airlines - Sheue Hui Lim; Minakshi Tripathi; Yin Ting Lim; Yu Xin Lim; Zi Jun Lim; Jun Liang Liu; Saurya Pratap Singh Sengar; Bhavnidhi Kansal; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
The rapid growth of low-cost carriers (LCCs) has intensified competition in the airline industry, making customer satisfaction a critical determinant of long-term sustainability. AirAsia, as a leading low-cost airline in the ASEAN region, must continuously understand the factors shaping passenger satisfaction. This study aims to examine the influence of service quality, price, convenience, and Customer Relationship Management (CRM) on customer satisfaction with AirAsia. A quantitative research design was employed using an online survey administered via Google Forms. Data were collected from 150 AirAsia passengers in Asia and analyzed using multiple regression analysis in SPSS. The results indicate that CRM has the strongest positive effect on customer satisfaction (? = 0.427, p 0.001), followed by price (? = 0.366, p 0.001) and service quality (? = 0.168, p 0.05). Convenience shows a positive but statistically insignificant relationship with customer satisfaction (? = 0.059, p 0.05). These findings suggest that relational and value-based factors play a more decisive role than functional convenience in the low-cost airline context. The study concludes that prioritizing CRM initiatives, alongside competitive pricing and consistent service quality, is essential for enhancing customer satisfaction and sustaining competitive advantage in the airline industry.